Valorisation of Products and Services from Biosphere Reserves of Cuba - Saez-Tonacca, L (Taylor and Francis, 2023)
The commercialisation of the agricultural biodiversity conserved by farmers linked to the Biosphere Reserves, as well as the valorisation of goods and services, have contributed to the diversification of food supply accessible to the Cuban population and to increase the income of farmer’s families. Food fairs recently introduced, as well as the dissemination of traditional recipes through brochures, have helped extend local cooking styles using traditional species and cultivars, thus increasing awareness of the value of farm products often unknown in urban areas. This chapter also describes how marketing promotes the linking of agricultural activities with tourism and recreational activities, increases the sustainable use of agrobiodiversity, and strengthens the value farmers attribute to traditionally conserved varieties. © 2024 selection and editorial matter, Urbano Fra Paleo and Leonor Castiñeiras; individual chapters, the contributors.